Seleção de peptídeos com potencial aplicação no diagnóstico de geohelmintíases - Jordânia Costa Pinto (2021)
Soil-transmitted helminths is among the most prevalent tropical diseases in the world, affecting approximately 1.5 billion people. Among the species of epidemiological importance, Ascaris lumbricoides, Trichiuris trichiura, Ancylostoma duodenale, Necator americanus and Strongyloides stercoralis stand out. These helminths are easily transmitted through ingestion of eggs or exposure to larvae, which are released into the feces of infected individuals. Helminthiasis has a major impact on public health, affecting the learning and development of children in school and pre-school age. In this context, the control of these parasites becomes necessary and the accurate diagnosis of these infections assumes a fundamental role in this process. The diagnosis of soil-transmitted helminths has been based on parasitological, molecular and immunological techniques. However, the available methods have proven to be flawed and difficult to apply in the field, requiring the improvement of current techniques and the search for new diagnostic methods that are sensitive, specific and that do not require specialized equipment. In the immunodiagnosis specific antibodies, pure or fractionated antigens of the parasite are used to detect infections. In recent years, the use of extract of pathogen antigens in immunodiagnostic assays has been replaced by peptides or recombinant proteins that have greater diagnostic specificity. The aim of the present study was to select conserved targets for the serological diagnosis of nematodes, as well as specific targets for epidemiologically relevant species in human infection. The predicted proteome was analyzed using in silico tools, based on the genes identified in the genome sequences of the nematodes of interest. From these analyzes, 1160 peptides were identified that showed a high score prediction for linear B cell epitopes, among which specific targets were selected and conserved among the species of interest and absent in other helminths. These peptides were subjected to reactivity tests by immunoblotting, with sera from individuals known to be positive for the species of interest, confirmed by parasitological techniques, in order to filter the most promising targets. In total, 107 target peptides were selected, 80 of which were specific (13 for hookworms, 41 for Ascaris sp., and 26 for S. stercoralis) and 27 conserved in more than one species. The various targets identified have great potential for improving the diagnosis of soil-transmitted helminths.